2006
DOI: 10.1677/joe.1.06480
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 induction of cyclin D1 expression in INS-1 β-cells: involvement of cAMP-responsive element

Abstract: Glucagon-like peptide-1 (GLP-1) and its analog exendin-4 (EX) have been considered as a growth factor implicated in pancreatic islet mass increase and -cell proliferation. This study aimed to investigate the effect of EX on cyclin D1 expression, a key regulator of the cell cycle, in the pancreatic -cell line INS-1. We demonstrated that EX significantly increased cyclin D1 mRNA and subsequently its protein levels. Although EX induced phosphorylation of Raf-1 and extracellular-signal-regulated kinase (ERK), both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(44 citation statements)
references
References 36 publications
(34 reference statements)
5
37
0
Order By: Relevance
“…Phosphorylation of Rb was also induced as previously reported (ESM Fig. 1a, b) [12]. Rb levels did not change in response to high glucose, supporting its response specifically to exendin-4.…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…Phosphorylation of Rb was also induced as previously reported (ESM Fig. 1a, b) [12]. Rb levels did not change in response to high glucose, supporting its response specifically to exendin-4.…”
Section: Resultssupporting
confidence: 87%
“…Adult pancreatic islet cells are mostly in the quiescent/G 1/0 state but can re-enter cell cycle following appropriate stimuli. For example, the glucagon-like peptide-1 (GLP-1) analogue, exendin-4, stimulates beta cell proliferation [11,12] while preventing alpha cell expansion [13,14]. However, the mechanisms by which GLP-1 mediates these divergent effects in alpha and beta cells are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings suggest a differentiated response of ␤-cells to extracellular growth factors with cyclin A2 being responsive to the cAMP-PKA-CREB-CBP pathway, whereas the D-type cyclins possibly respond to growth factor stimuli other than cAMP or PI 3-kinase (36). Previous reports have suggested that cyclins D1 and D2 respond to the cAMP pathway in in vitro cell systems (37)(38)(39). We do not find any evidence for exendin-4 or CREB-CBPmediated elevation in D-type cyclins.…”
Section: Exendin-4 Stimulation Of Cyclin A2mentioning
confidence: 56%
“…CREM repressor activity is regulated by gene expression rather than by posttranslational modification (32,33). A functional CRE is also present in CCND1 (34)(35)(36) at a location identical to that in CCND2; however, an analogous CRE is not present in CCND3. Together, these observations demonstrate a mechanism by which kinetin riboside can specifically suppress cyclin D2 and D1, but not D3, blocking gene transcription induced by diverse direct or indirect cis-or trans-activating signals (Supplemental Figure 5).…”
Section: Discussionmentioning
confidence: 99%